Analisis Faktor-Faktor yang Mempengaruhi Audit Delay: Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2020-2022 - Romadon, Ahmad Sahri; Mohklas (STIE Widya Manggala, 2024)
Research aims to determine the factors that influence audit delay. The independent variables consist of company size (X1), profitability (X2), solvency (X3), and audit opinion (X4). The dependent variable is audit delay (Y).This sampling method is to use purposive sampling. Based on predetermined criteria, a sample of 13 companies was obtained. This research was conducted over a period of 3 years, so the total sample is 39 companies. The type of data used is secondary data taken from the company's financial reports. The analysis technique used in this research is multiple linear regression using the SPSS 25 program application. The research results show that company size has a positive effect on audit delay, profitability (ROA) has a significant negative effect on audit delay, solvency (DER) has no effect on audit delay, while audit opinion has a significant negative effect on audit delay.